Negative outcomes and mortality in the frail elderly undergoing major surgery: which risk factors have the greatest impact? - Castillo Muñoz, Dania Nilbeth (2023)
The elderly, often frail, are patients susceptible to numerous complications, both immediate and in the short, medium and long term, following surgical interventions. Depending on their comorbidities, a comprehensive approach should be taken to achieve the best condition of the organs prior to surgery and attempt to maintain it during and after the intervention. Considering the statistical strength of negative outcomes, specifically mortality in elderly patients undergoing major surgery, is truly a challenge. This even extends to other fields such as bioethics, raising a dilemma about dysthanasia when resorting to certain risky interventions in those with a fearful life prognosis. Recently, interesting evidence estimating the incidence, mortality risk and factors associated with negative outcomes in elderly patients undergoing major surgery has been published, suggesting possible modifications in decision-making algorithms for future clinical practice guidelines insurgery. The objective of this review is to analyze updated evidence on which risk factors would have the greatest impact on negative outcomes and mortality in elderly patients undergoing major surgery. A literature search was conducted usingthe search terms “Major Surgery” and “Elderly,” in addition to synonyms, in the PubMed, ScienceDirect, Web of Science and MEDLINE databases. In general surgery and subspecialties, it is very complex to determine precise risk factors that canbe extrapolated to all surgical scenarios due to the complexity and specificity of certain organs and procedures. Evidence has found that frail adults undergoing surgery for colorectal cancer, liver metastasis, lung cancer, pancreatic disease andesophageal cancer have the longest hospital stays, and overall mortality is higher in those undergoing oncologic surgery.However, both physical and mental integrity are associated with worse outcomes, and surgical prehabilitation could positively impact this situation by improving functional reserve and post-surgical recovery time.